Well log reconstruction via spatio-temporal and frequency-aware networks: A parallel dual-MFA-KAN approach - Hui-Ling Chu; Ya-Juan Xue; Zhe-Ge Liu; Yu-Jia Pu (Journal of Applied Geophysics, 2026)

Dual-swirl micro-combustor for enhanced overall micro thermophotovoltaic system performance: optimizing temperature uniformity and system efficiency - Yonghong Wu; Yunfei Yan; Chenghua Zhang; Chang Liu; Junzhe Huang; Ge Pu; Xuelin Zhao (Fuel, 2026)

Integrated sludge resources hierarchical recovery: enhancing VFAs production through pilot scale liquid-state anaerobic fermentation by sludge residues-based biochar - Jing Zhang; Dong-Shan Yang; Jia-Yu Yang; Yun-Yi Song; Nan Wu; Tian Pu; Ge Zhu; Hong-Bo Liu; He Liu (Bioresource Technology, 2026)

An integrated glycan probe-based colorimetric biosensor for glycoprotein analysis - Jiazhu Pu; Shiao Yang; Ying Deng; Yining Zhao; Weikang Ge; Sha Zhu; Genxi Li (Analytica Chimica Acta, 2026)

Investigating Microbial Communities and Metabolic Dynamics in Jiupei from Cellars of Different Ages: An Integrated Amplicon and Metabolomic Analysis of Mianrou-Style Baijiu - Longyun Zhang; Chun Pu; Congzhi Zhang; Fengxue Guo; Jiaojiao Song; Xiangyang Ge; Yan Xu (Food Bioscience, 2026)

A cepstrum-guided 2D-VMD–TOPSIS framework for seismic gas-bearing reservoir detection - Yu-Jia Pu; Ya-Juan Xue; Zhe-Ge Liu (Applied Geophysics, 2026)

Differential responses of soil microbial biomass and diversity to long-term phosphorus fertilization: A global meta-analysis - Jiahao Ge; Xiaoyi Han; Xinyue Lei; Qixuan Wang; Pengyue Wu; Nanhai Zhang; Yuying Guo; Pu Yang; Baili Feng; Jinfeng Gao (Agriculture, Ecosystems & Environment, 2026)

Energy Absorption Model and Mechanism of Abrasive Water Jet Cutting on Sandstone Under Stress Based on Cutting Striations - Yiyu Lu; Houhan Pu; Qinglin Deng; Zhaolong Ge; Zhuolin Shi; Jianming Shangguan; Yuhuai Cui; Zhi Yao; Yunliang Wang (Rock Mechanics and Rock Engineering, 2026)

Iron-based nanozymes: From mechanisms to functional applications - Jia-Ming Wang; Kai-Zheng Feng; Pu-Ge Yu; Haoan Wu; Ming Ma; Yu Zhang (Chemical Engineering Journal, 2026)

A powdery biohybrid nano‑silver sensor based on phycoerythrin and carbon nanotubes for visual detection of Hg2+ in aquatic products - Chuanxu Liu; Xiangyu Lan; Changzhuo Zheng; Qinghao Ge; Xiaolong Han; Yang Pu; Wenjun Li (Algal Research, 2026)

Seasonal characteristics of atmospheric oxidizing capacity at environmental background area in North China from long-term field observations of O3, HONO and HCHO - Shuangshuang Ge; Zhiqiang Ma; Hailiang Zhang; Hanyu Zhang; Weiwei Pu; Yulu Qiu; Jinlong Hou; Chao Liu; Yucong Guo; Fan Dong; Di He; Liyan Zhou; et al. (Atmospheric Environment, 2026)

Co-gasification coupled with steam reforming of inseparable livestock biowastes for green hydrogen-rich syngas production - Jiarui Zhu; Qiuhan Pu; Liang Wang; Ge Kong; Zengjian Guo; Ru Sun; Guanyu Zhang; Xin Zhang; Xuesong Zhang; Lujia Han (Journal of Environmental Chemical Engineering, 2026)

Soil amendments improved physiological characteristics, grain yield, and water use efficiency of common buckwheat under multi-year continuous cropping - Qi Wang; Xiaoyi Han; Qixuan Wang; Minlong Du; Xinyue Lei; Jiahao Ge; Rong Zhong; Chenxi Wan; Xiaoli Gao; Pu Yang; Jinfeng Gao (European Journal of Agronomy, 2026)

Effect of Dry–Wet Cycling on the Abrasive Water Jet Cutting Performance of Green Sandstone - Zhaolong Ge; Zhuolin Shi; Qinglin Deng; Jianming Shangguan; Zhi Yao; Yuhuai Cui; Houhan Pu (Rock Mechanics and Rock Engineering, 2026)

Ecological effects and strategies of Spartina alterniflora Loisel. removal in China - Zhanbin Luo; Fu Chen; Xi-En Long; Jing Ma; Jiyou Wei; Yudi Guo; Yanfeng Zhu; Yongjun Yang; Xiaoping Ge; Yanyan Kang; Ming Zou; Lei Liu; et al. (Environmental Impact Assessment Review, 2026)

Nitrogen fertilizer strategies modulate gaseous nitrogen losses and improve maize yield and nitrogen use efficiency under saline-alkali stress in coastal reclaimed farmland - Xiaoqing Wang; Jiayi Xie; Wenjing Li; Lijie Pu; Pengjun Chen; Jijun Han; Chenliang Du; Sihua Huang; Rui Zhang; Rui Zhong; Ye Yuan; Jiahao Zhai; et al. (Soil and Tillage Research, 2026)

Attributing GHG emissions to individual facilities using multi-temporal hyperspectral images: Methodology and applications - Yichi Zhang; Ge Han; Yiyang Huang; Huayi Wang; Hongyuan Zhang; Zhipeng Pei; Yuanxue Pu; Haotian Luo; Jinchun Yi; Tianqi Shi; Siwei Li; Wei Gong (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

TS-TCN: a deep learning model for ultra-short-term outdoor air temperature forecasting in complex terrain with small sample size - Shun Wu; Jie Shao; Ge Li; Xiushu Pu; YuanChang Dong; Tao Du; Jinrong Kang; Bu Zhao (Energy and Buildings, 2026)

Aspirin Attenuates the Pathogenesis of Amyotrophic Lateral Sclerosis by Inhibiting the Activities of Microglia in a NF-κB-dependent Complement System-deactivating Mechanism - Tong-Qi Ge; Xiao-Yuan Ma; Pei-Pei Guan; Pu Wang (Molecular Neurobiology, 2026)

A novel deep learning system for STEMI prognostic prediction from multi-sequence cardiac magnetic resonance - Yifan Chen; Meng Jiang; Chao Xia; Hang Zhao; Panpan Ke; Sheng Chen; Heng Ge; Keran Li; Xu Wang; Yufei Wang; Yezi Chai; Qiming Liu; et al. (Science Bulletin, 2025)

High-performance antifouling electrochemical aptsensor based on a Y-shaped glycopeptide and platinum nanoparticles for detecting aflatoxin B1 in food - Cheng Zhang; Xujun Pu; Xian Chen; Jinzhi Liang; Kun Ge; Yangyue Ding; Lunzhao Yi; Ying Gu; Shuo Wang (Food Chemistry, 2025)

Selective kernel convolution with global attention mechanism for multitask change detection in optical and SAR images - Tonggen Yang; Liang Huang; Bo-Hui Tang; Zhitao Fu; Zhen Zhang; Zhongxi Ge; Man Zhang; Siming Pu (Earth Science Informatics, 2025)

Microalgae-based removal of pharmaceutically active compounds (PhACs) from wastewater: Mechanisms and applications - Ye Lin; Xue Pu; Jingyuan Xia; Xiyang Lu; Heyang Hu; Jiawei Bai; Fuyuan Guo; Shijian Ge; Shuang Qiu (Algal Research, 2025)

Decoding soil resilience: The role of eco-corona in alleviating toxicity for aged tire wear particles and benzalkonium chloride (C12) co-exposure - Bei Jiang; Yunhong Pu; Shengnan Shi; Zhaobo Chen; Dongxue Hu; Hui Ge; Shiming Cui; Yifan Wang; Pengcheng Zhang; Zihan Wang (Journal of Hazardous Materials, 2025)

Cracking the code of CO2 Photoreduction: Band engineering in BN for methane selectivity - Zhen Ge; Pengxin Pu; Haisong Feng; Mengjie Yu; Guanyi Zhang; Tianyong Liu; Xin Song; Shiquan Zhao; Lei Wang; Yusen Yang; Yibo Dou; Min Wei; et al. (Chemical Engineering Journal, 2025)

Dynamic and high methane emission flux in pond and lake aquaculture - Jiayu Zhao; Mi Zhang; Yini Pu; Lei Jia; Wei Xiao; Zhen Zhang; Pei Ge; Jie Shi; Qitao Xiao; Xuhui Lee (Journal of Hydrology, 2025)

Enhanced syngas selectivity over LaFeO3 oxygen carriers by A-site defect engineering in biomass chemical looping gasification - Yunlong Xia; Ge Pu; Jiale Wu; Qianhui Yang; Ruikang Zhou; Jie Wang; Jie Gao (Journal of Environmental Chemical Engineering, 2025)

Outer membrane vesicles from Pseudomonas aeruginosa induce autophagy-regulated pyroptosis in THP-1 cells - Jing Ge; Yaoyang Liu; Tianqi Wu; Sitian Yi; Jiang Pu; Juan Gu; Feng Wang; Juan Yu (Archives of Microbiology, 2025)

Quantifying restored riparian buffer delineation accuracy and detectability in multitemporal imagery - Ge Pu; Lindi J. Quackenbush; John C. Stella (Ecological Engineering, 2025)

Spatiotemporal distribution patterns of large and medium-sized mammals in a biodiversity hotspot: mplications for conservation - Wenqiang Hu; Xueyou Li; Kenneth Otieno Onditi; Hongjiao Wang; Wenyu Song; Zhechang Hu; Changzhe Pu; Mingjing Pu; Yun Xiong; Suhua Yang; Lin Zhu; Jianqiang Yin; et al. (Biological Conservation, 2025)

Treadmill Exercise Enhances Post-Stroke Functional Recovery in Mice via the CX3CL1/CX3CR1 Signaling Pathway - Yangyang Ge; Xiaoke Dou; Pu Chen; Jiayi Chen; Maosha Dai; Shanglong Yao; Yun Lin (Molecular Neurobiology, 2025)

High selectivity syngas generation by double perovskite oxygen carriers La2Fe2-xCoxO6 for chemical looping steam methane reforming - Yunlong Xia; Mengliang Gao; Ge Pu; Xingqiang Lu; Jie Gao; Jiale Wu; Qianhui Yang (Journal of Environmental Chemical Engineering, 2024)

Optimizing herbicide types and concentrations: Crucial elements for achieving intensive cultivation of common buckwheat - Qi Wang; Xiaona Wang; Liming Yang; Youxiu Chen; Jiahao Ge; Jincai Tao; Chenxi Wan; Pu Yang; Pengke Wang; Jinfeng Gao (Crop Protection, 2024)

Constructing Ni/ZnMOx composite metal oxide adsorbents with excellent desulfurization capacity and thermal stability for reactive adsorption desulfurization - Pu Dai; Mengya Guo; Hui Ge; Caimei Fan; Xuekuan Li; Xiuquan Liu; Junpeng Feng; Rui Li; Mingxing Tang (Fuel, 2024)

Aerosol interference with open-path eddy covariance measurement in a lake environment - Lei Jia; Mi Zhang; Wei Xiao; Yini Pu; Zhen Zhang; Hengxin Bao; Pei Ge; Jie Shi; Yang He; Fuyu Yang; Kelly Aho; Peter Raymond; et al. (Agricultural and Forest Meteorology, 2024)

Mobile measurement background quantification methods for determining local traffic emissions and background source contributions to ammonia - Weiwei Pu; Yingruo Li; Di He; Fan Dong; Jin Wu; Xiangxue Liu; Yulu Qiu; Shuangshuang Ge; Zhiqiang Ma (Atmospheric Environment, 2024)

Effects of black-odorous water bodies on the physiological ecology of Vallisneria natans and its attached biofilm microbial community - Tong Pu; Yili Ge; Mian Wu; Dabing Ge; Aiping Wu; Nazish Aijaz; Zhenrong Huang (Journal of Water Process Engineering, 2024)

Inhalation exposure to polystyrene nanoplastics induces chronic obstructive pulmonary disease-like lung injury in mice through multi-dimensional assessment - Sheng Yang; Tianyi Zhang; Yiling Ge; Lihong Yin; Yuepu Pu; Geyu Liang (Environmental Pollution, 2024)

Characteristics of PM2.5 hygroscopicity and the influences of water-soluble ions during haze events in Beijing - Shuangshuang Ge; Jie Su; Pusheng Zhao; Ju Li; Shijie Liu; Yulu Qiu; Weiwei Pu; Zhiqiang Ma (Atmospheric Environment, 2024)

Ferroptosis participated in inhaled polystyrene nanoplastics-induced liver injury and fibrosis - Yiling Ge; Sheng Yang; Tianyi Zhang; Saisai Gong; Xin Wan; Yuxin Zhu; Yifei Fang; Chengyu Hu; Fei Yang; Lihong Yin; Yuepu Pu; Zaozao Chen; et al. (Science of The Total Environment, 2024)

A dynamic harmonic regression approach to estimating groundwater evapotranspiration based on diurnal groundwater-level fluctuations - Jinting Huang; Jiawei Wang; Yangxiao Zhou; Tuo Fang; Bohan Ning; Ge Song; Tian Huang; Linghua Li; Zhan Yang; Qiu lv; Fang Pu; Zongze Li; et al. (Hydrogeology Journal, 2024)

The hepatotoxicity assessment of micro/nanoplastics: A preliminary study to apply the adverse outcome pathways - Yiling Ge; Sheng Yang; Tianyi Zhang; Xin Wan; Yuxin Zhu; Fei Yang; Lihong Yin; Yuepu Pu; Geyu Liang (Science of The Total Environment, 2023)

Boron Alleviates the Aluminum Toxicity in Tartary Buckwheat by Regulating Antioxidant Defense System and Maintaining Osmotic Balance - Jiahao Ge; Qi Wang; Xiaoying Xu; Xinhui Lei; Jincai Tao; Feng Gao; Xiaoli Gao; Pu Yang; Jinfeng Gao (Journal of Soil Science and Plant Nutrition, 2023)

Semiconductors modified gourd-shaped hollow PtNi and their directional electron and mass transfer effects - Fu-Fei Pu; Yu-Xuan Xiao; Xiong Yang; Fei Yu; Lei Xia; Jiang-Bo Chen; Lu Wu; Jing-Jing Xie; Wen-Ying Zhao; Yu Liu; Li-Ying Wang; Jie Ying; et al. (Chemical Engineering Journal, 2023)

Efficacy of transplant insecticides against black cutworm Agrotis ipsilon (Lepidoptera: Noctuidae) in tobacco - Pingping Liu; Jingxin Zhang; Huifang Shen; Qiyun Yang; Xiaoming Pu; Dayuan Sun; Baiyi Ge; Birun Lin (Crop Protection, 2023)

Sentinel supervised lung-on-a-chip: A new environmental toxicology platform for nanoplastic-induced lung injury - Sheng Yang; Tianyi Zhang; Yiling Ge; Yanping Cheng; Lihong Yin; Yuepu Pu; Zaozao Chen; Geyu Liang (Journal of Hazardous Materials, 2023)

As a Potential Therapeutic Target, C1q Induces Synapse Loss Via Inflammasome-activating Apoptotic and Mitochondria Impairment Mechanisms in Alzheimer’s Disease - Pei-Pei Guan; Tong-Qi Ge; Pu Wang (Journal of Neuroimmune Pharmacology, 2023)

Protective efficacy of recombinant proteins AMA1 and IMP1 in rabbits infected with Eimeria intestinalis - Jie Xiao; Wei He; Changming Xiong; Ge Hao; Jiayan Pu; Hao Chen; Liwen Xu; Yuhua Zhu; Yongjun Ren; Guangyou Yang (Veterinary Parasitology, 2023)

Evaluation of a novel carbon-based micro-nano zero-valent iron composite for immobilization of heavy metals in soil - Song Guo; Huifen Yang; Qiwei Sun; Ge Zhang; Tong Zhao; Yichen Zhou; Xuan Li; Pu Gao (Journal of Environmental Chemical Engineering, 2023)

A Sedimentary Facies-Based Method to Control Water Hazards in the Roof of Deep Jurassic Coals - Yang Wang; Yonghui Wu; Qin Ge; Zhiguo Pu; Jinhui Liu; Yanhong Zhang; Xiangjian Xie (Mine Water and the Environment, 2023)

The role of N6-methyladenosine methylation in environmental exposure-induced health damage - Yanlu Feng; Tong Liu; Siyi Xu; Yiyi Ren; Yiling Ge; Lihong Yin; Yuepu Pu; Geyu Liang (Environmental Science and Pollution Research, 2022)

Differentiation of Algal Blooms and Aquatic Vegetation in Chinese Lakes Using Modified Vegetation Presence Frequency Index Method - Jing Pu; Kaishan Song; Ge Liu; Zhidan Wen; Chong Fang; Junbing Hou; Yunfeng Lv (Chinese Geographical Science, 2022)

FTO mediated ERBB2 demethylation promotes tumor progression in esophageal squamous cell carcinoma cells - Fangfang Zhao; Fangfang Ge; Minghua Xie; Zhenyu Li; Chunbao Zang; Lingsuo Kong; Youguang Pu; Xucai Zheng; Yiao Tan (Clinical & Experimental Metastasis, 2022)
N 6 -methyladenosine (m 6 A) is the most prevalent and internal modification that occurs in the messenger RNAs of eukaryotes. However, knowledge of the impact of these modifications on gene expression regulation remains limited. By using the in vitro MeRIP-seq and RNA-seq assays, we discovered that the mRNA demethylase FTO was significantly up-regulated in esophageal squamous cell carcinoma (ESCC) tissues and cells. Knockdown of FTO drastically suppressed the proliferation, migration, and invasion of ESCC cells. Furthermore, by using transcriptome-wide m 6 A-seq and RNA-seq assays, we identified ERBB2 is the target of FTO, which acts in concert in ESCC tumorigenesis and metastasis. Moreover, loss and gain functional studies suggested that the m 6 A reader YTHDF1 stabilizes ERBB2 mRNA via decoding the m 6 A modification. All these results uncovered a new signaling cascade, including FTO, YTHDF1, and ERBB2, which finely regulates the ESCC progression.

Nutritional Profile and Bioremediation of Tropical Marine Aquaculture with an Integrated Microalgae and Bacteria Symbiosis - Ruiyang Ma; Shiyu Xie; Huiting Jia; Linhai Pu; Licheng Peng; Chengjun Ge (Water, Air, & Soil Pollution, 2022)

A Preliminary Study on Silver Isotopic Composition in Polymetallic Ore Deposits in Eastern China - Ge Dong; Hai-Zhen Wei; Yuanfeng Zhu; Xi Liu; Qi Guo; Wei Pu; Yibo Lin; Junlin Wang (Journal of Earth Science, 2022)

Bifidobacterium bifidum TMC3115 Can Characteristically Influence Glucose and Lipid Profile and Intestinal Microbiota in the Middle-Aged and Elderly - Ke Wang; Xiaohong Yu; Yi Li; Yun Guo; Lin Ge; Fangfang Pu; Xinying Ma; Wenjing Cui; Francesco Marrota; Fang He; Ming Li (Probiotics and Antimicrobial Proteins, 2019)

A pathogenesis-related protein 10 gene PnPR10–3 was involved in molecular interaction between Panax notoginseng and Fusarium solani - Bifeng Tang; Xin Li; Limei Pu; Qin Zhao; Xiuming Cui; Feng Ge; Diqiu Liu (Australasian Plant Pathology, 2019)

Rectified-Linear-Unit-Based Deep Learning for Biomedical Multi-label Data - Pu Wang; Ruiquan Ge; Xuan Xiao; Yunpeng Cai; Guoqing Wang; Fengfeng Zhou (Interdisciplinary Sciences: Computational Life Sciences, 2017)

Rapid and Sensitive Detection of Listeria monocytogenes by Loop-Mediated Isothermal Amplification - Meng-Jun Tang; Sheng Zhou; Xiao-Yan Zhang; Jun-Hua Pu; Qing-Lian Ge; Xiu-Jun Tang; Yu-Shi Gao (Current Microbiology, 2011)

The efficacy of FMD vaccine reduced non-structural proteins with a mAb against 3B protein - Dong Li; Zai-Xin Liu; Pu Sun; Yong-Liang Li; Zeng-Jun Lu; Mei-Na Tian; Ying-Li Chen; Bao-Xia Xie; Hui-Fang Bao; Yuan-Fang Fu; Yi-Mei Cao; Ping-Hua Li; et al. (Veterinary Research Communications, 2010)

Temporal and spatial patterns of NDVI and their relationship to precipitation in the Loess Plateau of China - Tianming Wang; Xiaojun Kou; Youcai Xiong; Pu Mou; Jianguo Wu; Jianping Ge (International Journal of Remote Sensing, 2010)

Retinoid X receptor agonists inhibit phorbol-12-myristate-13-acetate (PMA)-induced differentiation of monocytic THP-1 cells into macrophages - Lei Zhou; Ling-hong Shen; Liu-hua Hu; Heng Ge; Jun Pu; Da-jun Chai; Qin Shao; Li Wang; Jin-zhang Zeng; Ben He (Molecular and Cellular Biochemistry, 2010)

Magnetic cell sorting and flow cytometry sorting methods for the isolation and function analysis of mouse CD4+ CD25+ Treg cells - Hang Yan; Chen-guang Ding; Pu-xun Tian; Guan-qun Ge; Zhan-kui Jin; Li-ning Jia; Xiao-ming Ding; Xiao-ming Pan; Wu-jun Xue (Journal of Zhejiang University-SCIENCE B, 2009)

Spatial-temporal dynamics of regional convergence at County level in Jiangsu - Ying-xia Pu; Rong-hua Ma; Ying Ge; Xing-yuan Huang (Chinese Geographical Science, 2005)

Measurement of agglomeration economies at County level in Jiangsu Province - Ying Ge; Ying-xia Pu; Shi-mou Yao (Chinese Geographical Science, 2005)

Identification of 27 Porphyra lines (Rhodophyta) by DNA fingerprinting and molecular markers - Manli Weng; Bo Liu; Demin Jin; Qingkai Yang; Ge Zhao; Jiahai Ma; Pu Xu; Delin Duan; Bin Wang (Journal of Applied Phycology, 2005)